Ground improvement of non-cohesive soil using nanoparticles, specifically, laponite - Siddique, Shumsun Nahar (My University, 2024)
Ground improvement through densification is a widely used techniques to mitigate the risk of liquefaction and significant soil deformations. Traditional site stabilization techniques have certain limitations such as insufficient field treatment, substantial disturbances, environmental pollution, and high costs. However, incorporating nanoparticles into ground improvement techniques can lessen these negative impacts, offering a more efficient and environmentally friendly alternative. This study examines the characteristics of laponite, a promising soil improvement nanoparticle, when it is mixed with non-cohesive soil under full saturated conditions. The findings revealed that laponite is both environmental-friendly and biologically inert. Even a small amount of laponite significantly reduces the generation of pore water pressure under static loadings due to its good rheological properties as a transparent gel. Additionally, the modulus of elasticity of sand-laponite specimens is nearly double that of pure sand. The swelling strain of compacted laponite increases over time and as the concentration of laponite increased in specimens. Laponite also effectively restricts the migration of contaminants and reduces soil permeability due to its repeated swelling performance. Moreover, the damping ratio of treated samples is higher compared to untreated sand samples. The damping ratio begins to reduce after reaching its peak and eventually reaches equilibrium in case of sand+ laponite samples. The coefficient of permeability is significantly reduced with the presence of small amounts of laponite in sand samples. The compressive behaviour of laponite hydrogel indicates that laponite hydrogels exhibit the nonlinear stress-strain relationships which represents typical viscoelastic characteristics. This research provides novel insights into the improvement and modification of the properties of non-cohesive soil (sand) elaborately in the presence of laponite, demonstrating its potential as an effective ground improvement material.
Keywords: Laponite; Chlorophyll content; Pore water pressure; Hydrogel; Piezoceramics; Half- power bandwidth method